The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1167/iovs.07-1004
|View full text |Cite
|
Sign up to set email alerts
|

Mild Hypoxia Impairs Chromatic Sensitivity in the Mesopic Range

Abstract: In the mesopic range, mild hypoxia impairs chromatic sensitivity progressively with reducing luminance. Binocular summation of chromatic signals is consistent and independent of the luminance channel. The CAD test is highly sensitive to mild congenital and acquired color vision deficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 28 publications
4
28
1
1
Order By: Relevance
“…As pointed out recently [45], it is important to have sensitive and objective criteria that experts can use to decide whether small changes in vision in older subjects can be attributed entirely to normal aging or reflect early signs of retinal pathology. Since visual performance at lower light levels is more compromised in patients with early signs of ocular pathology [4] and the effects of mild acute hypoxia in normal subjects are also more detectable at lower light levels [5,6,46,47], it may be desirable to assess changes in visual performance over a range of light levels and not just photopic vision under optimum conditions. Indeed, if the HR index does reflect retinal susceptibility to disease, and hence hypoxia, imposed mild systemic hypoxia may exacerbate the loss of chromatic sensitivity as reflected in the HR index , more so in older subjects and/or those with more severe damage to the retina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As pointed out recently [45], it is important to have sensitive and objective criteria that experts can use to decide whether small changes in vision in older subjects can be attributed entirely to normal aging or reflect early signs of retinal pathology. Since visual performance at lower light levels is more compromised in patients with early signs of ocular pathology [4] and the effects of mild acute hypoxia in normal subjects are also more detectable at lower light levels [5,6,46,47], it may be desirable to assess changes in visual performance over a range of light levels and not just photopic vision under optimum conditions. Indeed, if the HR index does reflect retinal susceptibility to disease, and hence hypoxia, imposed mild systemic hypoxia may exacerbate the loss of chromatic sensitivity as reflected in the HR index , more so in older subjects and/or those with more severe damage to the retina.…”
Section: Discussionmentioning
confidence: 99%
“…Vision at low light levels is also compromised by imposed mild levels of hypoxia in healthy young subjects [5,6]. Other studies have shown that healthy normal observers who are carriers of the CFH, LOC387715, and HRTA1 genotypes and are considered to be of high risk of developing age-related maculopathy later in life perform significantly worse in the mesopic range in some visual tasks, but not at higher light levels [7].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a fair degree of individual variability, losses in color discrimination are primarily along the tritan axis and begin to occur at oxygen concentrations that are equivalent to an altitude of 2400 m (∼8; 000 ft) at mesopic light levels. The discrimination losses begin to occur at photopic light levels as the altitude increases beyond 3000 m (∼9; 000 ft), with more marked losses occurring above 4000 m (∼13; 100 ft) [1][2][3][4][5][6][7][8][9][10]. In addition to the color discrimination losses along the tritan axis at higher altitudes, the Nagel anomaloscope settings tend to require more green to match yellow, and there may be a relative decrease in the sensitivity to green light when measured using heterochromatic flicker photometry, especially at conditions equivalent to altitudes above 4000 m [2][3][4][5][6]11].…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of two studies [9,11], subjects participating in these hypoxia experiments all had normal color vision (NCV). In one of these studies, Schmidt reported that hypoxia produced subtle effects on the red-green color matches made by NCV and individuals with congenital anomalous trichromatic red-green defects (DCV) using the anomaloscope [11].…”
Section: Introductionmentioning
confidence: 99%
“…A four-alternative, forced-choice procedure is employed to measure the subject's thresholds for detection of colour signals in 16 directions in colour space, while ensuring that the subject cannot make use of any residual luminance contrast signals. 13 The Nidek Microperimeter (Nidek Technologies, Padova, Italy) was used to quantify macular sensitivity and fixation. It incorporates an eye tracker to compensate for eye movements and allows automated follow-up examination at the same retinal loci and also allows colour fundus image registration by infra-red camera (451 field of view).…”
Section: Assessmentsmentioning
confidence: 99%